Developmental toxicology - An integral part of safety evaluation of new drugs - Ujházy, Eduard; Mach, Mojmír; Dubovický, Michal; Navarová, Jana; Brucknerová, Ingrid (Biomedical papers, 2005)
The thalidomide tragedy stimulated an intense research in the etiology, prevention and treatment of congenital malformations. The Government requires that drugs and food additives be evaluated pre-clinically for toxicity, including developmental toxicity, before being marketed. The number of compounds which must be tested has increased dramatically with the continuous development of therapeutic, cosmetic and food additive chemicals. Such tests include: in vitro studies which can serve as efficient pre-screens to rank chemicals for further batteries of in vivo tests on pregnant animals. However, the safety of any drug would be determined only by a post-marketing epidemiological survey. Taking into account the altered susceptibility to different drugs in a pregnant individual, it could be said that administration of any drug during the first trimester is an experiment in human teratology.
Keywords: Developmental toxicology/Teratology/Screening tests/Biomodels